Positive electrode active material, positive electrode, and rechargeable lithium battery
By using lithium nickel-manganese composite oxide as positive electrode active substances in rechargeable lithium batteries, and adjusting their composition and surface coating, the problems of cobalt supply shortage and high voltage side reactions are solved, and high capacity is achieved. Long cycle life and good high voltage performance.
Patent Information
- Application Number
- CN202411056034.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-03
- Filing Date
- 2024-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
In the existing rechargeable lithium batteries, there is a shortage of supply of positive electrode active substances containing rare metal cobalt, and it is easy to react side effects with the electrolyte under high voltage conditions, resulting in a decrease in cycle life.
Using positive electrode active substances including lithium nickel-manganese composite oxides, the capacity, energy density and cycle life of the electrode are improved by adjusting the content of nickel and manganese and the design of the surface coating, and side reactions under high voltage are suppressed.
It achieves relatively high capacity and high energy density, extends the cycle life of the battery, and reduces side reactions under high voltage conditions, improving the overall performance of the battery.
Smart Images

Figure CN119447217A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2023-0101765 filed in the Korean Intellectual Property Office on August 3, 2023, the entire contents of which are incorporated herein by reference. Technical Field
[0003] One or more embodiments of the present disclosure are directed to a positive electrode active material, a positive electrode including the positive electrode active material, and a rechargeable lithium battery including the positive electrode. Background Art
[0004] Portable information devices (such as cellular phones, laptop computers, smart phones, etc.) and / or electric vehicles have used rechargeable lithium batteries with relatively high energy density and relative portability as driving power sources. Recently, research has been actively conducted to use rechargeable lithium batteries with relatively high energy density as driving power sources for hybrid vehicles and / or electric vehicles and / or as power storage power sources for home power storage units and / or power walls.
[0005] Various positive electrode active materials have been studied to realize rechargeable lithium batteries for these desired applications. Among them, lithium nickel oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides and lithium cobalt oxides are mainly used as positive electrode active materials. However, although the demand and utilization of rechargeable lithium batteries with large size, relatively high capacity or relatively high energy density have increased rapidly recently, the supply of positive electrode active materials containing rare metal cobalt is expected to be in serious shortage. For example, because cobalt is expensive and there are not many remaining reserves, it is necessary and desirable to develop positive electrode active materials that exclude cobalt or reduce the cobalt content (e.g., amount). Summary of the invention
[0006] One or more aspects of embodiments of the present disclosure relate to a positive electrode active material comprising a lithium nickel manganese composite oxide (reducing the cost (e.g., price) of the positive electrode material while ensuring relatively high capacity and relatively high energy density characteristics, and improving high voltage performance by inhibiting or reducing side reactions with an electrolyte at relatively high voltages), a positive electrode comprising the positive electrode active material, and a rechargeable lithium battery comprising the positive electrode. Additional aspects will be set forth in part in the subsequent description and in part will be apparent from the description, or may be understood by practicing the presented embodiments of the present disclosure.
[0007] In one or more embodiments, the positive electrode active material includes: a first positive electrode active material including a lithium nickel manganese-based composite oxide having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on 100 mol% of total metals other than lithium included in the first positive electrode active material and in the form of a plurality of secondary particles each including a plurality of primary particles (e.g., each prepared by aggregating a plurality of primary particles); and a second positive electrode active material including a nickel content (e.g., amount) greater than 100 mol% based on 100 mol% of total metals other than lithium included in the second positive electrode active material. or equal to about 60 mol % and in the form of a lithium nickel manganese composite oxide in the form of a plurality of individual particles (e.g., a plurality of individual particles each in the form of an integral particle), wherein the second positive electrode active material includes a coating on (e.g., arranged on) the surface of each of these individual particles and containing aluminum and yttrium, and based on 100 mol % of the total metal other than lithium in the second positive electrode active material, the aluminum content of the coating (e.g., the amount of aluminum) is about 0.1 mol % to about 2 mol % and the yttrium content of the coating (e.g., the amount of yttrium) is about 0.1 mol % to about 1 mol %.
[0008] In one or more embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material.
[0009] In one or more embodiments, a rechargeable lithium battery includes the aforementioned positive electrode, negative electrode, and electrolyte.
[0010] The positive electrode active material according to one or more embodiments increases or maximizes capacity while minimizing or reducing production costs, ensures long cycle life characteristics, and inhibits side reactions with electrolytes that can operate at relatively high voltages. Even under relatively high voltage operating conditions, rechargeable lithium batteries using the positive electrode active material can also exhibit relatively high initial charge / discharge capacity and efficiency, and can achieve long cycle life characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] The above and other aspects, features and advantages of certain embodiments of the present disclosure will become more apparent from the following description taken in conjunction with the accompanying drawings.
[0012] Figure 1 FIG. 1 is a schematic diagram schematically illustrating a rechargeable lithium battery according to one or more embodiments of the present disclosure.
[0013] Figure 2 is a scanning electron microscope (SEM) image of the first positive electrode active material of Example 1 of the present disclosure.
[0014] Figure 3: is a SEM image of the second positive electrode active material of Example 1 of the present disclosure.
[0015] Reference numerals
[0016] 100: Rechargeable lithium battery 10: Positive electrode
[0017] 20: Negative electrode 30: Separator
[0018] 40: electrode assembly 50: shell DETAILED DESCRIPTION
[0019] Hereinafter, example embodiments will be described in more detail so that those skilled in the art can easily implement them. However, the present disclosure may be implemented in many different forms and is not to be construed as limited to the example embodiments set forth herein.
[0020] The terms used in this article are only used to describe the embodiments and are not intended to limit the present disclosure. As used herein, the singular forms "a", "an", and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise. Further, when describing the embodiments of the present disclosure, the use of "may" refers to "one or more embodiments of the present disclosure".
[0021] As used herein, "combinations thereof" may refer to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like, of the components.
[0022] In this document, it should be understood that terms such as “comprise(s) / comprising”, “include / including” or “have / has / having” are intended to indicate the presence of implemented features, numbers, operations, elements and / or their (e.g., any appropriate) combination, but this does not exclude the possibility of the presence or addition of one or more other features, numbers, operations, elements and / or their (e.g., any appropriate) combination.
[0023] In the accompanying drawings, the thickness of layers, films, panels, regions, etc. may be exaggerated for clarity, and throughout the present disclosure, the same reference numerals represent the same elements, and for the sake of brevity, a repeated description thereof may not be provided. It will be understood that if (for example, when) an element (such as a layer, film, region, or substrate) is referred to as being "on" another element (such as a layer, film, region, or substrate), it may be directly on the other element (such as a layer, film, region, or substrate), or there may also be intervening elements. In contrast, if (for example, when) an element (such as a layer, film, region, or substrate) is referred to as being "directly on" another element (such as a layer, film, region, or substrate), there are no intervening elements.
[0024] In one or more embodiments, the “layer” herein includes not only a shape or film formed on the entire surface but also a shape or film formed on a partial surface if (for example, when) viewed from a plan view.
[0025] In one or more embodiments, the average particle size can be measured by methods well known to those skilled in the art, for example, by a particle size analyzer (e.g., HORIBA, LA-950 laser particle size analyzer), or by a transmission electron microscope (TEM) or a scanning electron microscope (SEM). In one or more embodiments, the average particle size value can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles in each particle size range, and calculating from the data. Unless otherwise specified, the average particle size (D 50 ) may refer to the diameter of particles of which the cumulative volume accounts for 50% by volume in a particle size distribution. 50 Refers to the average diameter (or size) of particles whose cumulative volume corresponds to 50 vol% in a particle size distribution (e.g., cumulative distribution), and refers to the value of the particle size corresponding to 50% from the smallest particle when the total number of particles is 100% in a distribution curve accumulated in the order of the smallest particle size to the largest particle size. In one or more embodiments, as used herein, if (e.g., when) no definition is provided in another manner, the average particle diameter (D 50 ) refers to the diameter of particles of which the cumulative volume is 50% by volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscope image. In the present disclosure, when the particles are spherical, "diameter" indicates the average particle diameter, and when the particles are non-spherical, "diameter" indicates the major axis length.
[0026] In this article, "or" is not interpreted as an exclusive meaning, for example, "A or B" is interpreted as including A, B, A+B, etc. Further, as used in this article, the term "and / or" includes any and all combinations of one or more related listed items. When before / after a list of elements, expressions such as "at least one of", "one of", and "selected from" modify the entire list of elements without modifying the individual elements of the list. For example, "at least one of a, b, and c", "selected from at least one of a, b, and c", "selected from at least one of a to c", etc. may indicate only a, only b, only c, both a and b (e.g., at the same time), both a and c (e.g., at the same time), both b and c (e.g., at the same time), all a, b, and c, or variations thereof. The " / " used in this article may be interpreted as "and" or "or" depending on the circumstances.
[0027] As used herein, the term "metal" is interpreted as a concept including ordinary metals, transition metals, and metalloids (semimetals).
[0028] Positive electrode active material
[0029] In one or more embodiments, the positive electrode active material includes: a first positive electrode active material including a lithium nickel manganese-based composite oxide having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on 100 mol% of total metals other than lithium included in the first positive electrode active material and in the form of a plurality of secondary particles each including a plurality of aggregated primary particles (e.g., each prepared by aggregating a plurality of primary particles); and a second positive electrode active material including a nickel content (e.g., amount) greater than or equal to about 60 mol% based on 100 mol% of total metals other than lithium included in the second positive electrode active material. A lithium nickel manganese composite oxide having an amount greater than or equal to about 60 mol % and in the form of a plurality of individual particles (e.g., a plurality of individual particles each in the form of an integral particle), wherein the second positive electrode active material includes a coating on (e.g., arranged on) the surface of each of these individual particles and containing aluminum and yttrium, and based on 100 mol % of the total metal other than lithium in the second positive electrode active material, the aluminum content of the coating (e.g., the amount of aluminum) is about 0.1 mol % to about 2 mol % and the yttrium content of the coating (e.g., the amount of yttrium) is about 0.1 mol % to about 1 mol %.
[0030] Since the price of rare metal cobalt has risen sharply recently, it is necessary and desirable to develop positive electrode active materials that exclude cobalt or reduce the cobalt content (e.g., amount). Among these positive electrode active materials, positive electrode active materials with olivine crystal structure (such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), lithium manganese iron phosphate (LMFP), etc.) or positive electrode active materials with spinel crystal structure (such as lithium manganese oxide (LMO), etc.) are limited in achieving relatively high capacity due to the small amount of available lithium in their structure. The layered nickel-manganese positive electrode active material has excellent or appropriate capacity and efficiency characteristics due to the relatively high available lithium capacity in its structure, making it suitable as a material for a relatively high capacity battery. However, as cobalt, which plays a key role in the layered structure, is removed, the structural stability is reduced, the resistance is increased, and it becomes difficult to ensure long cycle life characteristics. In addition, the layered nickel-manganese positive electrode active material excluding cobalt may have the problem of accelerating the side reaction with the electrolyte under relatively high voltage and relatively high temperature conditions, resulting in increased gas generation and deterioration of the cycle life characteristics of the related battery.
[0031] In one or more embodiments of the present disclosure, a mixture of a first positive electrode active material including a lithium nickel manganese type composite oxide in the form of secondary particles and a second positive electrode active material in the form of a plurality of single particles of a lithium nickel manganese type composite oxide is applied, and a specific coating material of the present disclosure is applied to each of the first positive electrode active material and the second positive electrode active material in a specific content (e.g., amount) in one or more embodiments to provide a positive electrode active material exhibiting relatively high capacity and relatively high energy density, relatively long cycle life, and improved high voltage performance.
[0032] The average particle size (D 50 ) may be larger than the average particle size (D 50 ). In this article, the first positive electrode active material may be expressed as large particles, and the second positive electrode active material may be expressed as small particles. By appropriately mixing large particles and single particles in the form of secondary particles, the capacity and energy density of the lithium nickel manganese positive electrode can be maximized or increased, and the cycle life characteristics and durability of the lithium nickel manganese positive electrode can be improved.
[0033] In one or more embodiments, the average particle size (D 50 ) means the diameter of particles accounting for 50% by volume of the cumulative volume in a particle size distribution obtained by randomly measuring the sizes (diameters or major axis lengths) of about 20 particles in a scanning electron microscope image.
[0034] In one or more embodiments, the average particle size (D 50 ) may be, for example, about 10 micrometers (μm) to about 20 μm, about 10 μm to about 18 μm, or about 12 μm to about 16 μm. The average particle size (D 50 ) may be, for example, about 0.5 μm to about 8 μm, about 1 μm to about 7 μm, about 1.5 μm to about 6 μm, or about 2 μm to about 5 μm. When the average particle size of each positive electrode active material satisfies the above range, a relatively high capacity and a relatively high energy density can be achieved.
[0035] In one or more embodiments, based on a total of 100wt% of the first positive electrode active material and the second positive electrode active material, the amount of the first positive electrode active material included may be about 60wt% to about 95wt%, for example, about 70wt% to about 90wt%. Based on a total of 100wt% of the first positive electrode active material and the second positive electrode active material, the amount of the second positive electrode active material included may be about 5wt% to about 40wt%, for example, about 10wt% to about 30wt%. When the mixing ratio of the first positive electrode active material and the second positive electrode active material satisfies the above range, the energy density can be increased while maximizing or increasing the capacity.
[0036] The lithium nickel manganese composite oxide of the first positive electrode active material and the lithium nickel manganese composite oxide of the second positive electrode active material may be the same or different from each other. Based on 100mol% of the total metal other than lithium in the lithium nickel manganese composite oxide, the nickel content (e.g., amount) in each lithium nickel manganese composite oxide may be independently greater than or equal to about 60mol%, such as about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If the nickel content (e.g., amount) satisfies the above range, even if the cobalt content (e.g., amount) is reduced, a relatively high capacity can be achieved and structural stability can be increased.
[0037] For example, in one or more embodiments, based on 100 mol% of the total metal other than lithium in the lithium nickel manganese composite oxide, the manganese content (e.g., amount) may be greater than or equal to about 15 mol%, for example, about 15 mol% to about 40 mol%, about 15 mol% to about 35 mol%, about 15 mol% to about 30 mol%, or about 20 mol% to about 30 mol%. If the manganese content (e.g., amount) satisfies the above range, the positive electrode active material can improve structural stability while achieving a relatively high capacity.
[0038] In one or more embodiments, the layered lithium nickel manganese composite oxide in each of the first positive electrode active material and the second positive electrode active material may be a lithium nickel manganese aluminum composite oxide further including aluminum in addition to nickel and manganese. If the lithium nickel manganese composite oxide includes aluminum, it is beneficial to maintain a stable layered structure even if the cobalt element is excluded from the structure. Based on 100 mol% of the total metal other than lithium in the lithium nickel manganese aluminum composite oxide, the aluminum content (e.g., amount) may be greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, for example, about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 1.9 mol%. If the aluminum content (e.g., amount) satisfies the above range, even if cobalt is excluded, a stable layered structure can be maintained, the problem of structural collapse caused by charging and discharging can be suppressed or reduced, and the long cycle life characteristics of the positive electrode active material can be achieved.
[0039] The lithium nickel manganese-based composite oxide of the first positive electrode active material and the lithium nickel manganese-based composite oxide of the second positive electrode active material may each be independently represented by Chemical Formula 1.
[0040] Chemical formula 1
[0041] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1
[0042] In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 It may be one or more elements selected from boron (B), barium (Ba), calcium (Ca), cerium (Ce), chromium (Cr), iron (Fe), magnesium (Mg), molybdenum (Mo), niobium (Nb), silicon (Si), tin (Sn), strontium (Sr), titanium (Ti), vanadium (V), tungsten (W) and zirconium (Zr), and X may be one or more elements selected from fluorine (F), phosphorus (P) and sulfur (S).
[0043] In Chemical Formula 1, in some embodiments, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2. In one or more embodiments, the lithium nickel manganese composite oxide represented by Chemical Formula 1 may include aluminum, and in these embodiments, it may satisfy 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29, for example, it may satisfy 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 < z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29.
[0044] In Chemical Formula 1, for example, in some embodiments, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8, or 0.7 ≤ x1 ≤ 0.79; 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39, or 0.2 ≤ y1 ≤ 0.3; 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02, or 0.01 < z1 ≤ 0.019; and 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w2 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1, or 0 ≤ w1 ≤ 0.09.
[0045] In one or more embodiments, the lithium nickel manganese composite oxide may be a cobalt-free compound that does not include cobalt or includes a very small amount of cobalt. For example, based on 100 mol% of the total metals other than lithium included in their respective lithium nickel manganese composite oxides, the lithium nickel manganese composite oxides of the first positive electrode active material and the second positive electrode active material may each independently have a cobalt content (e.g., amount) of about 0 mol% to about 0.01 mol%.
[0046] The first positive electrode active material
[0047] In one or more embodiments, the concentration of aluminum in the secondary particles of the first positive electrode active material not including the coating can be substantially uniform. For example, aluminum is uniformly (substantially uniformly) dispersed in the particles, with no concentration gradient from the center of each of these particles to the surface of each of these particles, or no concentration difference inside and outside the particles (e.g., between particles). Accordingly, the positive electrode active material can be prepared by not additionally doping aluminum but using aluminum raw materials to prepare a precursor, wherein nickel-manganese-aluminum hydroxides can be used as precursors and synthesize composite oxides. For example, regardless of the position of the primary particles, the aluminum content (e.g., amount) inside the primary particles can be equal or similar. If the primary particles are selected at random positions in the cross section of the secondary particles, and the aluminum content (e.g., amount) is measured inside the primary particles rather than at their interfaces, the aluminum content (e.g., amount) can be the same / similar / substantially uniform regardless of the position of the primary particles (i.e., whether the primary particles are close to the center of the secondary particles or close to the surface of the secondary particles). In this structure, even if cobalt is absent or present in a very small amount, a stable layered structure can be maintained and aluminum byproducts or aluminum aggregates are not generated, thereby simultaneously improving the capacity, efficiency and cycle life characteristics of the positive electrode active material.
[0048] The first positive electrode active material according to one or more embodiments may further include a coating layer on (e.g., located on) the surface of each of the secondary particles and comprising aluminum and zirconium. The first positive electrode active material includes an aluminum-rich zirconium layer on the surface to effectively inhibit or reduce side reactions with the electrolyte at relatively high voltages, thereby improving capacity and cycle life characteristics at relatively high voltages.
[0049] Based on 100 mol% of the total metals other than lithium in the first positive electrode active material, the aluminum content (e.g., the amount of aluminum) of the coating may be about 0.1 mol% to about 2 mol%. In one or more embodiments, based on 100 mol% of the total metals other than lithium in the first positive electrode active material, the aluminum content (e.g., the amount) of the coating in the first positive electrode active material may be, for example, about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%. The content (e.g., the amount) of aluminum in the coating may be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. If the aluminum content (e.g., the amount) in the coating satisfies this range, the coating may be formed to have a substantially uniform and thin thickness, which does not increase the resistance of the positive electrode active material, but effectively inhibits or reduces side reactions with the electrolyte, and improves the cycle life characteristics of the rechargeable lithium battery at a relatively high voltage.
[0050] Based on 100 mol% of the total metal other than lithium in the first positive electrode active material, the zirconium content (e.g., amount) of the coating in the first positive electrode active material may be, for example, about 0.05 mol% to about 1 mol%, about 0.1 mol% to about 1 mol%, about 0.1 mol% to about 0.9 mol%, about 0.1 mol% to about 0.8 mol%, or about 0.1 mol% to about 0.6 mol%. The zirconium content (e.g., amount) in the coating may be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. If the zirconium content (e.g., amount) satisfies the range, a satisfactory coating may be formed without degrading the capacity of the positive electrode active material or increasing the resistance, but effectively inhibiting or reducing the side reaction with the electrolyte, and additionally improving the capacity characteristics and cycle life characteristics under relatively high voltage operating conditions.
[0051] In one or more embodiments, the coating of the first positive electrode active material may further include yttrium in addition to aluminum and zirconium, and in these embodiments, the content (e.g., amount) of yttrium may be from about 0.1 mol% to about 1 mol% based on 100 mol% of total metals other than lithium in the first positive electrode active material.
[0052] The coating of the first positive electrode active material may be in the form of a film that continuously surrounds the surface of the secondary particle, for example, it may be in the form of a shell that surrounds the entire surface of the secondary particle. This is different from a structure in which only a portion of the surface of the secondary particle is partially coated. According to one or more embodiments, the coating may be formed to completely cover the surface of the secondary particle, and may be formed to be very thin and substantially uniform in thickness, so that the positive electrode active material does not increase resistance and / or does not reduce capacity, improves structural stability, effectively inhibits side reactions with the electrolyte, reduces the amount of gas generated under relatively high voltage and relatively high temperature conditions, and achieves long cycle life characteristics.
[0053] In one or more embodiments, the thickness of the coating of the first positive electrode active material may be about 30 nanometers (nm) to about 500nm, for example, about 30nm to about 450nm, about 30nm to about 400nm, about 30nm to about 350nm, about 30nm to about 300nm, about 30nm to about 250nm, about 30nm to about 200nm, about 30nm to about 150nm, about 50nm to about 500nm, about 80nm to about 500nm or about 100nm to about 500nm. If the coating meets this thickness range, the structural stability of the positive electrode active material can be improved without increasing resistance and / or reducing capacity due to the coating, and the side reaction with the electrolyte can be effectively suppressed or reduced. The thickness of the coating can be measured by, for example, time-of-flight secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS) or energy dispersive spectroscopy (EDS) analysis, for example, by TEM-EDS line profile.
[0054] The coating of the first positive electrode active material may be thin and substantially uniform in thickness, at the level of tens of nanometers to hundreds of nanometers. For example, in one or more embodiments, the deviation of the coating thickness in a positive electrode active material particle (e.g., a secondary particle) may be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the deviation of the coating thickness refers to the deviation of the coating thickness in a positive electrode active material particle. For example, the thickness of about 10 points in the electron microscope image of the cross section of a single positive electrode active material particle can be measured to calculate the arithmetic mean, and then the absolute value of the difference between one data and the arithmetic mean is divided by the arithmetic mean and multiplied by 100 to calculate the deviation of the coating thickness. The fact that the deviation or standard deviation of the coating thickness meets the above range refers to a coating with substantially uniform thickness being well formed in the form of a film on the surface of the positive electrode active material particle. Accordingly, the structural stability of the positive electrode active material is improved, the side reaction with the electrolyte is effectively suppressed or reduced, and the resistance increase and / or capacity reduction due to the coating can be minimized or reduced.
[0055] In one or more embodiments, during the coating formation process, aluminum may diffuse into the secondary particles. Accordingly, the positive electrode active material according to one or more embodiments may further include a grain boundary coating portion, which contains aluminum and is located on the surface of each of the primary particles inside each of the secondary particles. The internal portion of the secondary particle may refer to the entire internal portion except the surface of the secondary particle, or the internal portion may be a region of about 60% of the length from the center of the secondary particle to the surface of the secondary particle at most the radius (i.e., the distance from the surface of the secondary particle to the center of the secondary particle). The grain boundary coating is a concept different from the coating on the surface of the secondary particle, and refers to the coating portion formed on the surface of each of the primary particles inside each of the secondary particles. The presence of the grain boundary coating portion can be confirmed by SEM-EDS analysis of the cross section of the positive electrode active material. By forming (or providing) an aluminum grain boundary coating portion, the positive electrode active material can become more stable in structure, and the cycle life characteristics of the positive electrode active material can be improved.
[0056] The aluminum content (eg, amount) in the grain boundary coating portion is not particularly limited, and for example, in some embodiments, the aluminum content (eg, amount) in the grain boundary coating portion may be less than the aluminum content (eg, amount) in the coating.
[0057] On the other hand, in one or more embodiments, the aluminum content (e.g., amount) of the coating of the first positive electrode active material may be greater than the aluminum content of the coating of the second positive electrode active material, which will be described in more detail later. For example, in one or more embodiments, the ratio of the aluminum content (e.g., amount) of the coating of the first positive electrode active material to the aluminum content (e.g., amount) of the coating of the second positive electrode active material may be about 5:1 to about 2:1 or about 4:1 to about 2:1. In this article, the aluminum of the coating in the first positive electrode active material and the second positive electrode active material may not act as a resistor, but rather maximize or increase the capacity and cycle life characteristics at relatively high voltages and improve the structural stability of each layer.
[0058] Second positive electrode active material
[0059] A single particle of the second positive electrode active material refers to a single particle that exists alone without a grain boundary within the particle, is composed of one particle, and has a single particle, a monolithic structure, an integral structure or a non-aggregated particle in which the particles are not aggregated with each other in morphology but exist as independent phases, and can be expressed as a single particle (integral particle, single grain), such as a single crystal.
[0060] The second positive electrode active material includes a coating layer on (e.g., arranged on) the surface of a single particle and including aluminum and yttrium, wherein the aluminum content (e.g., the amount of aluminum) of the coating layer is about 0.1 mol% to about 2 mol% based on 100 mol% of the total metals other than lithium included in the second positive electrode active material, and the yttrium content (e.g., the amount of yttrium) of the coating layer is about 0.1 mol% to about 1 mol%. When the coating layer of the second positive electrode active material includes (e.g., simultaneously includes) both aluminum and yttrium and each satisfies the above content (e.g., amount) range, the initial discharge capacity and cycle life characteristics of the positive electrode active material at a relatively high voltage according to one or more embodiments can be maximized or increased.
[0061] In one or more embodiments, the content (e.g., amount) of aluminum in the coating of the second positive electrode active material may be about 0.1 mol% to about 2 mol%, for example, about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%, based on 100 mol% of the total metal other than lithium in the second positive electrode active material. This refers only to the content (e.g., amount) of aluminum included in the coating of the second positive electrode active material, and does not include the content (e.g., amount) of aluminum included in a single particle. The aluminum content (e.g., amount) in the coating can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. If the aluminum content (e.g., amount) in the coating layer of the second positive electrode active material satisfies these ranges, the coating layer may have a substantially uniform and thin thickness, which may not increase the resistance of the positive electrode active material, and effectively suppress or reduce the side reaction with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery under relatively high voltage and relatively high temperature conditions. For example, if the aluminum content (e.g., amount) of the coating layer of the second positive electrode active material is too much, a substantially uniform coating layer may not be formed, or the resistance may increase, which may reduce the charge / discharge efficiency and the cycle life characteristics, and if the aluminum content (e.g., amount) of the coating layer of the second positive electrode active material is too little, a coating layer of a suitable or appropriate thickness is not formed, and the effect of suppressing or reducing the side reaction with the electrolyte may be reduced.
[0062] In one or more embodiments, the yttrium content (e.g., the amount of yttrium) in the coating of the second positive electrode active material may be about 0.1 mol% to about 1 mol%, for example, about 0.1 mol% to about 0.9 mol%, about 0.1 mol% to about 0.8 mol%, about 0.1 mol% to about 0.6 mol%, about 0.1 mol% to about 0.4 mol%, or about 0.1 mol% to about 0.3 mol%, based on 100 mol% of the total metal other than lithium in the second positive electrode active material. If the yttrium content (e.g., amount) satisfies the above range, the positive electrode active material forms a good or suitable coating without reducing the capacity or increasing the resistance, thereby effectively inhibiting or reducing the side reaction with the electrolyte and effectively reducing the amount of gas generated under high voltage or high temperature conditions.
[0063] The second positive electrode active material includes (eg, simultaneously includes) both aluminum and yttrium in the coating layer, and may improve capacity characteristics and cycle-life characteristics at a relatively high voltage compared to an embodiment including only one of aluminum and yttrium.
[0064] The coating of the second positive electrode active material may be in the form of a film that continuously surrounds the surface of a single particle, or, for example, may be in the form of a shell that surrounds the entire surface of a single particle. This is different from a structure in which only a portion of the particle surface is partially coated. The coating according to one or more embodiments may be formed to have a very thin and substantially uniform thickness and completely cover the surface of a single particle, which neither increases the resistance of the positive electrode active material nor degrades the capacity, but exhibits improved structural stability, and can effectively inhibit or reduce side reactions with the electrolyte, thereby achieving long cycle life characteristics at relatively high voltages.
[0065] In one or more embodiments, the thickness of the coating of the second positive electrode active material may be about 30nm to about 500nm, such as about 30nm to about 450nm, about 30nm to about 400nm, about 30nm to about 350nm, about 30nm to about 300nm, about 30nm to about 250nm, about 30nm to about 200nm, about 30nm to about 150nm, about 50nm to about 500nm, about 80nm to about 500nm or about 100nm to about 500nm. If the coating of the second positive electrode active material meets these thickness ranges, the structural stability of the positive electrode active material can be improved without increasing resistance and / or reducing capacity due to the coating, and side reactions with the electrolyte can be effectively suppressed or reduced. The thickness of the coating can be measured by, for example, TOF-SIMS, XPS or EDS analysis, for example, it can be measured by TEM-EDS line profile.
[0066] The coating of the second positive electrode active material is thin and substantially uniform in thickness, within the range of tens of nanometers to hundreds of nanometers. For example, in one or more embodiments, the deviation of the coating thickness in a positive electrode active material particle (e.g., a single particle) may be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the deviation of the coating thickness refers to the deviation of the coating thickness in a positive electrode active material particle. For example, the thickness of about 10 points in the electron microscope image of the cross section of a single positive electrode active material particle can be measured to calculate the arithmetic mean, and then the absolute value of the difference between a measured data and the arithmetic mean is divided by the arithmetic mean and multiplied by 100 to calculate the deviation of the coating thickness. The fact that the deviation or standard deviation of the coating thickness meets the above range refers to a coating with substantially uniform thickness being well formed in the form of a film on the surface of the positive electrode active material particle. Accordingly, the structural stability of the positive electrode active material is improved, the side reaction with the electrolyte can be effectively suppressed or reduced, and the resistance increase and / or capacity reduction caused by the coating can be minimized or reduced.
[0067] In the coating layer of the second positive electrode active material, aluminum may exist in the form of a continuous film (eg, a substantially continuous film) and yttrium may exist in the form of an island shape due to the characteristics of each element.
[0068] In one or more embodiments, aluminum and yttrium may be mixed in one coating, wherein the aluminum may be present in the form of a continuous film (e.g., a substantially continuous film) and the yttrium may be present in the form of an island shape (e.g., individual islands), but the embodiments of the present disclosure are not limited thereto.
[0069] In one or more embodiments, aluminum and yttrium may each form (or provide) a separate layer. For example, in one or more embodiments, the second positive electrode active material may include: a first coating comprising aluminum and on (e.g., arranged on) the surface of each of these individual particles, and a second coating comprising yttrium and (e.g., arranged on) the first coating. Aluminum is first attached or adsorbed on the surface of a single particle to form (or provide) a first coating as a thin film, and yttrium is coated thereon to form (or provide) a second coating. In this article, in some embodiments, aluminum and yttrium may be mixed in the first coating and the second coating, but the first coating may be an aluminum-rich coating comprising aluminum as a main component, and the second coating may be a yttrium-rich coating comprising yttrium as a main component. In this article, in the second coating, yttrium may exist as an island shape (e.g., a separate island), but is not particularly limited thereto.
[0070] In one or more embodiments, the thickness of the first coating and the second coating is not particularly limited. However, the thickness of the first coating may be about 10nm to about 200nm, such as about 20nm to about 200nm, about 30nm to about 200nm, or about 30nm to about 180nm. The thickness of the second coating may be about 20nm to about 300nm, such as about 20nm to about 250nm, about 20nm to about 200nm, about 30nm to about 300nm, or about 50nm to about 300nm. If the respective thicknesses of the first coating and the second coating meet the above range, the structural stability of the positive electrode active material can be improved, the resistance will not be increased and / or the capacity will not be reduced due to the coating, and the cycle life characteristics at relatively high voltages can be improved by effectively suppressing or reducing the side reactions with the electrolyte.
[0071] The cobalt content (e.g., the amount of cobalt) in the positive electrode active material according to one or more embodiments may be, for example, less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, less than or equal to about 0.001 mol%, or, for example, about 0 mol% to about 0.01 mol%, based on 100 mol% of the total metals other than lithium included in the positive electrode active material. The positive electrode active material according to one or more embodiments may be, for example, a cobalt-free positive electrode active material.
[0072] In addition, in one or more embodiments, the positive electrode active material can be characterized as not containing sodium. Generally speaking, sodium ions can be used in the preparation process of the positive electrode active material, but according to the preparation method described in more detail later, positive electrode active material particles having a stable structure and a coating layer with substantially uniform thickness can be formed without using sodium ions.
[0073] Method for preparing positive electrode active material
[0074] In one or more embodiments, the method for preparing a positive electrode active material may include: (i) mixing a nickel-manganese composite hydroxide having a nickel content (e.g., nickel amount) greater than or equal to about 60 mol% of the total metal based on 100 mol% of the nickel-manganese composite hydroxide with a lithium raw material, and heat treating it to prepare a first positive electrode active material in the form of secondary particles made by aggregating multiple primary particles; (ii) mixing a nickel-manganese composite hydroxide having a nickel content (e.g., nickel amount) greater than or equal to about 60 mol% of the total metal based on 100 mol% of the nickel-manganese composite hydroxide with a lithium raw material, followed by heat treating to obtain a lithium nickel-manganese composite oxide in the form of multiple single particles, and adding the obtained lithium nickel-manganese composite oxide to a solution of an aluminum raw material and a yttrium raw material in an aqueous solvent, followed by mixing, drying, and reheating to prepare a second positive electrode active material, and (iii) mixing the first positive electrode active material with the second positive electrode active material. Herein, in the process of preparing the second positive electrode active material, the aluminum content (e.g., amount) in the aluminum raw material is about 0.1 mol% to about 2 mol% based on 100 mol% of the total metals other than lithium in the second positive electrode active material, and the yttrium content (e.g., amount) in the yttrium raw material is about 0.1 mol% to about 1 mol% based on 100 mol% of the total metals other than lithium in the second positive electrode active material. The aforementioned positive electrode active material can be prepared by this method.
[0075] In the process of preparing the first positive electrode active material and the second positive electrode active material, the nickel-manganese composite hydroxide may not contain cobalt or may contain a very small amount of cobalt, for example, it may be a cobalt-free nickel-manganese composite hydroxide, such as a cobalt-free nickel-manganese-aluminum composite hydroxide. The nickel-manganese composite hydroxide can be prepared by a general coprecipitation method.
[0076] Based on 100mol% of the total metal in the nickel-manganese composite hydroxide, the nickel content (e.g., amount) in the nickel-manganese composite hydroxide is greater than or equal to about 60mol%, such as about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If the nickel content (e.g., amount) satisfies the above range, even if the cobalt content (e.g., amount) is reduced, a relatively high capacity can be achieved, and structural stability can also be increased or maintained.
[0077] The manganese content (e.g., amount) in the nickel-manganese-based composite hydroxide may be about 10 mol% to about 40 mol%, about 10 mol% to about 39 mol%, about 10 mol% to about 35 mol%, about 10 mol% to about 30 mol%, about 10 mol% to about 29 mol%, about 15 mol% to about 39 mol%, about 20 mol% to about 39 mol%, or about 20 mol% to about 30 mol%, based on 100 mol% of total metals in the nickel-manganese-based composite hydroxide.
[0078] In one or more embodiments, if (for example, when) the nickel-manganese composite hydroxide further contains aluminum (when), the content (for example, amount) of aluminum may be greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, for example, about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 1.9 mol%, based on 100 mol% of the total metal in the nickel-manganese composite hydroxide. If the manganese content and aluminum content of the nickel-manganese composite hydroxide meet the above range, a relatively high capacity can be achieved, while the structural stability of the positive electrode active material can be increased, and the production price can be reduced to increase economic benefits.
[0079] Based on 100 mol% of total metals in the nickel-manganese composite hydroxide, the cobalt content (e.g., amount) in the nickel-manganese composite hydroxide may be less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%. The nickel-manganese composite hydroxide may be economical because it avoids the increase in unit cost caused by cobalt, maximizes capacity, and improves structural stability.
[0080] As an example, in one or more embodiments, the nickel-manganese-based composite hydroxide may be represented by Chemical Formula 2.
[0081] Chemical formula 2
[0082] Ni x2 Mn y2 Al z2 M 2 w2 (OH)2
[0083] In Chemical Formula 2, 0.6≤x2≤0.8, 0.1≤y2≤0.4, 0≤z2≤0.03, 0≤w2≤0.3, and 0.9≤x2+y2+z2+w2≤1.1, and M 2 It may be one or more elements selected from the group consisting of B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W and Zr.
[0084] In Chemical Formula 2, for example, in some embodiments, 0.6≤x2≤0.8, 0.1≤y2≤0.39, 0.01≤z2≤0.03, and 0≤w2≤0.29.
[0085] The nickel-manganese composite hydroxide may be in the form of particles, and the average particle size (D 50 ) may be about 10 μm to about 18 μm, about 11 μm to about 16 μm, or about 12 μm to about 15 μm.
[0086] In one or more embodiments, in the preparation process of the first positive electrode active material, aluminum is not additionally doped on the first positive electrode active material, but an aluminum raw material is used to prepare a precursor of a nickel-manganese-aluminum composite hydroxide, in which aluminum is uniformly dispersed in the structure. Such a precursor can be used to prepare a positive electrode active material that can stably maintain a layered structure despite repeated charging and discharging without the presence of cobalt, wherein no aluminum byproduct or aluminum aggregate is formed, thereby improving the capacity and efficiency characteristics and cycle life characteristics of the positive electrode active material.
[0087] In one or more embodiments, in the process of preparing the first positive electrode active material, the nickel-manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of about 1:0.9 to about 1:1.8 (e.g., about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2). The heat treatment after mixing can be carried out in an oxygen atmosphere, for example, at a temperature range of about 750°C to about 950°C, about 780°C to about 900°C, or about 810°C to about 890°C for about 2 hours to about 20 hours or about 4 hours to about 12 hours. By heat treatment, a lithium nickel-manganese composite oxide can be obtained.
[0088] The obtained lithium nickel manganese composite oxide may include about 60 mol % or more (e.g., about 60 mol % to about 80 mol %) of nickel based on 100 mol % of total metals in the lithium nickel manganese composite oxide, but may not include cobalt or include a very small amount of cobalt less than or equal to about 0.01 mol %.
[0089] The method for preparing a positive electrode active material according to one or more embodiments may further include obtaining a lithium nickel manganese composite oxide in the process of preparing a first positive electrode active material, and then coating the obtained lithium nickel manganese composite oxide. The lithium nickel manganese composite oxide has a significantly different residual lithium content (e.g., amount) and different surface characteristics from oxides having other compositions (e.g., conventional nickel oxides such as lithium nickel cobalt manganese composite oxides or lithium nickel cobalt aluminum composite oxides, etc.), and conventional coating methods cannot successfully form (or provide) a good or appropriate coating in the form of a substantially uniform film thereon. In one or more embodiments, a method for improving relatively high voltage characteristics by uniformly (substantially uniformly) forming (or providing) a very thin coating on the surface of a lithium nickel manganese composite oxide having a very small amount of cobalt and a nickel content (e.g., amount) greater than or equal to about 60 mol% is applied. For example, a coating according to one or more embodiments can be formed by adding and mixing an aluminum raw material to an aqueous solvent, adding and mixing a lithium nickel manganese composite oxide, and then drying and reheating the mixture. This can be referred to as a wet coating method.
[0090] The aqueous solvent may include distilled water, an alcohol solvent and / or (e.g., any appropriate) combination thereof. The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide and / or (e.g., any appropriate) combination thereof. For example, in one or more embodiments, the aluminum raw material may include aluminum sulfate, and in these embodiments, it is advantageous to form (or provide) a coating having a substantially uniform thickness on the surface of the lithium nickel manganese composite oxide particles. Based on 100 mol% of the total metal other than lithium in the first positive electrode active material, the aluminum content (e.g., amount) of the aluminum raw material may be designed to be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol% or about 0.8 mol% to about 1.3 mol%.
[0091] The solution obtained by mixing the aluminum raw material in an aqueous solvent may have a pH of about 1.5 to about 3.5 (e.g., about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2). The mixing and stirring of the lithium nickel manganese composite oxide and the aqueous solvent (in which the aluminum raw material is mixed) can be carried out for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5 (e.g., about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0). If these conditions are met, it is advantageous to form (or provide) a coating having a substantially uniform thickness.
[0092] Reheating can be understood as a process of forming (or providing) a coating, and can be performed, for example, in an oxygen atmosphere at a temperature range of about 700°C to about 850°C, about 750°C to about 840°C, or about 800°C to about 830°C for about 2 hours to about 20 hours or about 3 hours to about 10 hours.
[0093] In order to coat zirconium in addition to aluminum, reheating can be performed by adding a zirconium raw material to the product obtained after drying. The zirconium raw material may be, for example, zirconium oxide, and the zirconium raw material may be added so that the zirconium content (e.g., amount) is about 0.05 mol% to about 1 mol% based on about 100 mol% of the total metal other than lithium in the first positive electrode active material.
[0094] Similarly, in the process of preparing the second positive electrode active material, the nickel manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of about 1:0.9 to about 1:1.8 (e.g., about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2). After mixing, the heat treatment can be carried out under an oxygen atmosphere, for example, at about 750°C to about 950°C, about 780°C to about 900°C, or about 810°C to about 890°C for about 2 hours to about 20 hours or about 4 hours to about 12 hours. By heat treatment, a lithium nickel manganese composite oxide can be obtained. Based on 100 mol% of the total metal in the obtained lithium nickel manganese composite oxide, the obtained lithium nickel manganese composite oxide may include nickel in an amount greater than or equal to about 60 mol% (e.g., about 60 mol% to about 80 mol%), but does not include cobalt or includes a very small amount of cobalt less than or equal to about 0.01 mol%. In order to obtain the lithium nickel manganese-based composite oxide in the form of individual particles, a pulverization process may be further included.
[0095] The coating of aluminum and yttrium on the second positive electrode active material in the form of a plurality of individual particles may also not adopt a comparable coating method in the related art, but utilize a wet coating method according to one or more embodiments to ensure a satisfactory coating as a substantially uniform film. For example, a lithium nickel manganese composite oxide in the form of a plurality of individual particles is added to a solution in which an aluminum raw material and a yttrium raw material are mixed in an aqueous solvent, and then dried and reheated to prepare the second positive electrode active material.
[0096] More details about aqueous solvent and aluminum raw material can be independently the same as the aqueous solvent and aluminum raw material described above. Based on about 100mol% of the total metal other than lithium in the second positive electrode active material, the aluminum content (e.g., amount) of the aluminum raw material can be designed to be about 0.1mol% to about 2mol%, such as about 0.2mol% to about 1.9mol%, about 0.3mol% to about 1.8mol%, about 0.5mol% to about 1.5mol% or about 0.8mol% to about 1.3mol%. The yttrium raw material may include, for example, yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide and / or its (e.g., any appropriate) combination. Based on 100 mol% of the total metals other than lithium in the second positive electrode active material, the yttrium content (e.g., amount) of the yttrium raw material can be designed to be about 0.1 mol% to about 1 mol%, such as about 0.1 mol% to about 0.9 mol%, about 0.1 mol% to about 0.8 mol%, about 0.1 mol% to about 0.6 mol%, about 0.1 mol% to about 0.4 mol%, or about 0.1 mol% to about 0.3 mol%. Each of the coating raw materials is designed within a respective range to form (or provide) a coating having a substantially uniform and thin thickness (e.g., a scale of tens of nanometers to hundreds of nanometers), which can reduce gas generation in rechargeable lithium batteries under relatively high voltage operating conditions, and improve high capacity and long cycle life characteristics.
[0097] The solution obtained by mixing the aluminum raw material, the yttrium raw material and / or their (e.g., any appropriate) combination in an aqueous solvent may have a pH of about 1.5 to about 3.5 (e.g., about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2). The mixing and stirring of the lithium nickel manganese composite oxide and the aqueous solvent (in which the aluminum raw material and the yttrium raw material are mixed) may be performed for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5 (e.g., about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0). If these conditions are met, it is advantageous to form (or provide) a coating having a substantially uniform thickness.
[0098] Drying after the mixing process can be understood as a process for removing the solvent, and can be performed, for example, at about 40°C to about 240°C, about 100°C to about 220°C, or about 150°C to about 200°C. Reheating can be understood as a process for forming (or providing) a coating, for example, at about 700°C to about 850°C, about 750°C to about 840°C, or about 800°C to about 830°C under an oxygen atmosphere for about 2 hours to about 20 hours or about 3 hours to about 10 hours. In addition, the reheating temperature can be lower than the previous heat treatment temperature, and the reheating time can be the same as or shorter than the previous heat treatment time. Under these conditions, a desired or appropriate coating can be obtained by reheating under these conditions.
[0099] In some embodiments, a dry coating method may be applied to coat the second positive electrode active material of a single particle type with aluminum and yttrium. In the dry coating method, the coating raw materials may be, for example, aluminum oxide and yttrium oxide.
[0100] The first positive electrode active material and (with) the second positive electrode active material can be mixed in a weight ratio of about 60:40 to about 95:5 (e.g., about 70:30 to about 90:10). If mixed in this ratio, the capacity and cycle life characteristics of the positive electrode active material can be improved while maximizing or increasing the energy density.
[0101] Positive electrode
[0102] In one or more embodiments, the positive electrode may include a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the positive electrode active material described above. In some embodiments, in addition to the positive electrode active material described above, the positive electrode active material layer may further include other types (kinds) of positive electrode active materials. In one or more embodiments, the positive electrode active material layer may optionally further include a binder, a conductive material and / or a combination thereof (e.g., any appropriate).
[0103] According to one or more embodiments, the loading level of the positive electrode active material layer may be about 10 mg / cm 2 ~ about 40mg / cm 2 , for example about 10 mg / cm 2 ~about 30mg / cm 2 or about 10 mg / cm 2 ~about 20mg / cm 2. In one or more embodiments, the density of the positive electrode active material layer in the final pressed positive electrode may be about 3.5 g / cc to about 3.7 g / cc, for example, about 3.5 g / cc to about 3.6 g / cc or about 3.5 g / cc to about 3.58 g / cc. When the positive electrode active material according to one or more embodiments is applied, the implementation of the load level and density of such a positive electrode active material layer is facilitated, and the positive electrode satisfying the load level and density of the positive electrode active material layer within the above range is suitable for implementing a high-capacity, high-energy-density rechargeable lithium battery.
[0104] Binder
[0105] The binder improves the bonding properties between the positive electrode active material particles and between the positive electrode active material particles and the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin and nylon, but the embodiments of the present disclosure are not limited thereto.
[0106] Conductive Materials
[0107] A conductive material (e.g., an electronic conductor) may be included to provide electrode conductivity, and any conductive material may be used as the conductive material unless it causes a chemical change. Non-limiting examples of conductive materials may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; and / or (e.g., any appropriate) mixtures thereof.
[0108] Each content (eg, amount) of the binder and the conductive material may be about 0.5 wt % to about 5 wt % or about 0.5 wt % to about 3 wt % based on 100 wt % of the total weight of the positive electrode active material layer.
[0109] The positive electrode current collector may include an Al foil, but embodiments of the present disclosure are not limited thereto.
[0110] Rechargeable lithium battery
[0111] According to one or more embodiments of the present disclosure, a rechargeable lithium battery may include the aforementioned positive electrode, negative electrode, and electrolyte.
[0112] Rechargeable lithium batteries may be classified into cylindrical batteries, prismatic batteries, pouch-type batteries, coin-type batteries, etc. according to their shapes. Figure 1 Schematic diagram for explaining a rechargeable lithium battery according to one or more embodiments. Figure 1 , the rechargeable lithium battery 100 may include an electrode assembly 40 having a separator 30 interposed between a positive electrode 10 and a negative electrode 20, and a case 50 accommodated in the case 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown).
[0113] The rechargeable lithium battery according to one or more embodiments may be rechargeable at a relatively high voltage, or may be suitable for driving at a relatively high voltage. For example, in one or more embodiments, the charging voltage of the rechargeable lithium battery may be greater than or equal to about 4.45V, about 4.45V to about 4.7V, about 4.45V to about 4.6V, or about 4.45V to about 4.55V. By applying the positive electrode active material according to one or more embodiments, the rechargeable lithium battery can significantly reduce the amount of gas generated even (for example, when) charging at a relatively high voltage, and can also achieve relatively high capacity and long cycle life characteristics.
[0114] Negative electrode
[0115] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and the negative electrode active material layer may include a negative electrode active material, a binder, a conductive material, and / or (eg, any appropriate) combination thereof.
[0116] Negative electrode active material
[0117] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.
[0118] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, and / or (for example, any appropriate) combinations thereof as carbonaceous negative electrode active materials. Crystalline carbon may be amorphous, or natural graphite or artificial graphite in the form of flakes, sheets, spheres, or fibers (for example, in the form of fibers). Amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization products, calcined coke, etc.
[0119] Lithium metal alloys include alloys of lithium with a metal selected from sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), silicon (Si), antimony (Sb), lead (Pb), indium (In), zinc (Zn), barium (Ba), radium (Ra), germanium (Ge), aluminum (Al) and tin (Sn).
[0120] The material capable of doping / undoping lithium can be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material can include silicon, silicon-carbon composite, SiO x (0 < x ≤ 2), Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and / or their (e.g., any suitable) combination, such as magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), scandium (Sc), yttrium (Y), titanium (Ti), zirconium (Zr), hafnium (Hf), (Rf), vanadium (V), niobium (Nb), tantalum (Ta), dubnium (Db), chromium (Cr), molybdenum (Mo), tungsten (W), (Sg), technetium (Tc), rhenium (Re), (Bh), iron (Fe), lead (Pb), ruthenium (Ru), osmium (Os), (Hs), rhodium (Rh), iridium (Ir), palladium (Pd), platinum (Pt), copper (Cu), silver (Ag), gold (Au), zinc (Zn), cadmium (Cd), boron (B), aluminum (Al), gallium (Ga), tin (Sn), indium (In), thallium (Tl), germanium (Ge), phosphorus (P), arsenic (As), antimony (Sb), bismuth (Bi), sulfur (S), selenium (Se), tellurium (Te), polonium (Po), and / or their (e.g., any suitable) combination) and / or their (e.g., any suitable) combination. The Sn-based negative electrode active material can be Sn, SnO k (0 < k ≤ 2) (e.g., SnO2), Sn alloy, and / or their (e.g., any suitable) combination.
[0121] The silicon-carbon composite can be a composite of silicon in particulate form and amorphous carbon. The average particle size (D 50 ) of the silicon-carbon composite particles (e.g., secondary particles) can be, for example, about 0.5 micrometers (μm) to about 20 μm. According to one or more embodiments, the silicon-carbon composite can be in the form of silicon particles and amorphous carbon coated on the surface of each of the silicon particles. For example, in some embodiments, the silicon-carbon composite can include secondary particles (cores) in which silicon primary particles are assembled and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon can also be present between the silicon primary particles, e.g., each of the silicon primary particles can be coated with amorphous carbon. The secondary particles can be present dispersed in an amorphous carbon matrix.
[0122] The silicon-carbon composite may further include crystalline carbon. For example, in one or more embodiments, the silicon-carbon composite may include: a core including crystalline carbon and silicon particles, and an amorphous carbon coating on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, and / or a combination thereof (e.g., any suitable combination). The amorphous carbon may include soft carbon, hard carbon, mesophase pitch carbonization products, and / or calcined coke.
[0123] In one or more embodiments, if (e.g., when) the silicon-carbon composite includes silicon and amorphous carbon, then based on the total weight of 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon may be about 10 wt% to about 50 wt% and the content (e.g., amount) of amorphous carbon may be about 50 wt% to about 90 wt%. In one or more embodiments, if (e.g., when) the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, then based on the total weight of 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon may be about 10 wt% to about 50 wt%, the content (e.g., amount) of crystalline carbon may be about 10 wt% to about 70 wt%, and the content (e.g., amount) of amorphous carbon may be about 20 wt% to about 40 wt%.
[0124] In one or more embodiments, the thickness of the amorphous carbon coating may be about 5 nm to about 100 nm. The average particle size (D 50 ) of the silicon particles (primary particles) may be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may exist as silicon alone, in the form of a silicon alloy, or in the oxidized form of silicon. The oxidized form of silicon may be represented by SiO x (0 < x ≤ 2). In one or more embodiments, the atomic content (e.g., amount) ratio Si:O indicating the degree of oxidation may be about 99:1 to about 33:67. As used herein, if (e.g., when) no other definition is provided otherwise, the average particle size (D 50 ) indicates the diameter of the particles in which the cumulative volume in the particle size distribution is about 50 vol%.
[0125] In some embodiments, the Si-based negative electrode active material or the Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material or the Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed and used, their mixing ratio may be a weight ratio of about 1:99 to about 90:10.
[0126] Binder
[0127] The binder is used to bind the negative electrode active material particles well to each other, and also to bind the negative electrode active material to the negative electrode current collector. The binder may be a non-aqueous (e.g., water-insoluble) binder, an aqueous (e.g., water-soluble) binder, a dry binder, and / or (e.g., any appropriate) combination thereof.
[0128] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, and / or (eg, any suitable) combinations thereof.
[0129] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenol resin, epoxy resin, polyvinyl alcohol and / or (e.g., any suitable) combination thereof.
[0130] If (for example, when) an aqueous binder is used as a binder in the negative electrode active material layer, a cellulose compound capable of imparting viscosity may be further included. As the cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and an alkali metal salt thereof may be mixed and used. The alkali metal may be Na, K or Li.
[0131] The dry binder may be a polymer material capable of fiberization, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, and / or (eg, any appropriate) combinations thereof.
[0132] Conductive Materials
[0133] In one or more embodiments, a conductive material (e.g., an electronic conductor) may be included to provide and / or improve electrode conductivity, and any conductive material may be used as a conductive material unless it causes a chemical change. Non-limiting examples of conductive materials may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; and / or (e.g., any suitable) mixtures thereof.
[0134] Based on the total weight of 100wt% of the negative electrode active material layer, the content (e.g., amount) of the negative electrode active material may be about 95wt% to about 99.5wt%, and based on the total weight of 100wt% of the negative electrode active material layer, the content (e.g., amount) of the binder may be about 0.5wt% to about 5wt%. For example, in one or more embodiments, based on the total weight of 100wt% of the negative electrode active material layer, the negative electrode active material layer may include about 90wt% to about 99wt% of the negative electrode active material, about 0.5wt% to about 5wt% of the binder, and about 0wt% to about 5wt% of the conductive material.
[0135] Negative electrode current collector
[0136] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof, and may be in the form of foil, sheet or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 7 μm to about 10 μm.
[0137] Electrolyte
[0138] In one or more embodiments, the electrolyte for a rechargeable lithium battery may be an electrolyte that may include a non-aqueous organic solvent and a lithium salt.
[0139] The non-aqueous organic solvent is used as a medium for transmitting ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent may include carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents and / or (for example, any appropriate) combinations thereof.
[0140] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In one or more embodiments, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles (such as R-CN (wherein R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, and may include a double bond, an aromatic ring or an ether group, etc.)); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane, etc.); cyclopentane sulfone, etc.
[0141] The non-aqueous organic solvent may be used alone or in a mixture of two or more types (kinds), and if (for example, when) two or more types (kinds) are used in a mixed form, the mixing ratio may be suitably or appropriately adjusted according to the desired or appropriate battery performance, which is well known to those skilled in the art.
[0142] If (for example, when) a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.
[0143] In one or more embodiments, the non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, in some embodiments, a carbonate-based solvent and an aromatic hydrocarbon organic solvent may be mixed and used in a volume ratio of about 1:1 to about 30:1.
[0144] In one or more embodiments, the electrolyte may further include vinyl ethylene carbonate, vinylene carbonate, or ethylene carbonate-based compounds to improve the battery cycle life.
[0145] Non-limiting examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0146] The lithium salt dissolved in the non-aqueous organic solvent supplies lithium ions in the rechargeable lithium battery, ensures the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Non-limiting examples of the lithium salt may include selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+ 1SO2) (wherein x and y are integers of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFBOP) and lithium bis(oxalato)borate (LiBOB).
[0147] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has suitable or appropriate ion conductivity and viscosity, and thus excellent or appropriate performance may be achieved, and lithium ions may be efficiently moved.
[0148] Diaphragm
[0149] Depending on the type or kind of the rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, or a multilayer film of two or more layers thereof (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).
[0150] The membrane may include a porous substrate and a coating on one or both surfaces (e.g., opposite surfaces) (e.g., on both surfaces (e.g., opposite surfaces)) of the porous substrate, the coating comprising an organic material, an inorganic material and / or a combination thereof (e.g., any suitable one).
[0151] The porous substrate may be a polymer film formed by: any one selected from the group consisting of polymers polyolefins (such as polyethylene and / or polypropylene), polyesters (such as polyethylene terephthalate and / or polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyether ketones, polyarylether ketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fibers, and polytetrafluoroethylene (e.g., Teflon); or copolymers or mixtures of two or more thereof.
[0152] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0153] The organic material may include a (meth)acryl-based copolymer, which includes: a first structural unit derived from (meth)acrylamide; and a second structural unit including at least one of a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid or its salt.
[0154] The inorganic material may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and / or (e.g., any suitable) combination thereof, but the embodiments of the present disclosure are not limited thereto. The average particle size (D 50 ) may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.
[0155] An organic material and an inorganic material may be mixed in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.
[0156] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.
[0157] Examples and comparative examples of the present disclosure are described in more detail herein.However, the following examples are merely examples of the present disclosure, and the present disclosure is not limited to the following examples.
[0158] Example 1
[0159] 1. Preparation of positive electrode active material
[0160] (1) Preparation of the first positive electrode active material
[0161] Ni 0.75 Mn 0.23 Al 0.02 (OH)2 and LiOH were mixed in a molar ratio of 1:1.05 and then preliminarily heat-treated at 850°C for 8 hours in an oxygen atmosphere to prepare a first composite oxide in the form of secondary particles having Li 1.05 Ni 0.75 Mn 0.23 Al 0.02 O2 composition and an average particle size of about 14 μm (D 50).
[0162] After aluminum sulfate is added to the distilled water solvent, the first composite oxide is added thereto and mixed for about 20 minutes to 60 minutes. In this article, based on 100mol% of the total metals other than lithium in the first positive electrode active material, the aluminum content (e.g., amount) of aluminum sulfate is designed to be 1.0mol%. The solvent is removed from the mixed solution and then the remainder is dried at 190°C, after which zirconium oxide is dry mixed with it, and then, secondary heat treatment (i.e., reheating) is performed at 825°C under an oxygen atmosphere for 8 hours to obtain the first positive electrode active material. Based on 100mol% of the total metals other than lithium in the final first positive electrode active material, the zirconium content (e.g., amount) of zirconium oxide is designed to be 0.2mol%. Figure 2 is a scanning electron micrograph of the prepared first positive electrode active material.
[0163] (2) Preparation of the Second Positive Electrode Active Material
[0164] Ni 0.75 Mn 0.23 Al 0.02 (OH)2, LiOH and Al2O3 were mixed in a molar ratio of 1:1:0.02, and then heat treated at 850°C for 8 hours in an oxygen atmosphere to prepare a quartz crystal with an average particle size (D 50 ) in the form of a plurality of individual particles of about 3 μm having LiNi 0.7 Mn 0.2 Al 0.02 A second composite oxide with a composition of O2.
[0165] The second composite oxide, Al2O3 and Y2O3 are mixed and heat-treated at 825°C for 8 hours in an oxygen atmosphere to prepare a second positive electrode active material. Here, they are mixed so that the aluminum content (e.g., amount) in the coating is 0.4 mol% and the yttrium content (e.g., amount) in the coating is 0.1 mol% based on 100 mol% of the total metals other than lithium in the final second positive electrode active material. Figure 3 is a scanning electron micrograph of the prepared second positive electrode active material.
[0166] (3) Preparation of the final positive electrode active material
[0167] The final positive electrode active material (ie, positive electrode active material) was prepared by mixing the first positive electrode active material and the second positive electrode active material at a weight ratio of 7:3.
[0168] 2. Preparation of positive electrode
[0169] Based on the total amount of the positive electrode active material layer slurry, 98.5wt% of the positive electrode active material, 1.0wt% of the polyvinylidene fluoride binder and 0.5wt% of the carbon nanotube conductive material are mixed to prepare the positive electrode active material layer slurry, and the positive electrode active material layer slurry is coated on the aluminum foil positive electrode current collector, and then, dried and pressed to prepare the positive electrode. The density of the positive electrode active material layer in the final pressed positive electrode is about 3.52g / cc.
[0170] 3. Preparation of rechargeable lithium battery cells
[0171] Based on the total amount of the negative electrode active material layer slurry, 97.5wt% of graphite negative electrode active material, 1.5wt% of carboxymethyl cellulose and 1wt% of styrene-butadiene rubber were mixed in an aqueous solvent to prepare a negative electrode active material layer slurry. The negative electrode active material layer slurry was coated on a copper foil negative electrode current collector, and then dried and pressed to prepare a negative electrode.
[0172] A rechargeable lithium battery cell was prepared in a conventional method using a polytetrafluoroethylene separator and using an electrolyte prepared by dissolving 1M LiPF6 in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7.
[0173] Example 2
[0174] A positive electrode active material, a positive electrode, and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the second positive electrode active material was prepared by designing the content (e.g., amount) of yttrium in the coating to be 0.2 mol % based on 100 mol % of the total metals other than lithium in the final second positive electrode active material.
[0175] Example 3
[0176] A positive electrode active material, a positive electrode, and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the second positive electrode active material was prepared by designing the content (e.g., amount) of aluminum in the coating to be 0.2 mol % based on 100 mol % of the total metals other than lithium in the final second positive electrode active material.
[0177] Example 4
[0178] A positive electrode active material, a positive electrode, and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the second positive electrode active material was prepared by designing the content (e.g., amount) of aluminum in the coating to be 0.6 mol % based on 100 mol % of the total metals other than lithium in the final second positive electrode active material.
[0179] Example 5
[0180] A positive electrode active material, a positive electrode, and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the first positive electrode active material was prepared by designing the content (e.g., amount) of zirconium in the coating to be 0.1 mol % based on 100 mol % of the total metal excluding lithium in the final first positive electrode active material.
[0181] Example 6
[0182] A positive electrode active material, a positive electrode, and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the first positive electrode active material was prepared by designing the content (e.g., amount) of zirconium in the coating to be 0.3 mol % based on 100 mol % of the total metal excluding lithium in the final first positive electrode active material.
[0183] Comparative Example 1
[0184] A positive electrode active material, a positive electrode, and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the second positive electrode active material was prepared by not using yttrium oxide during coating, ie, no yttrium was included in the coating of the second positive electrode active material.
[0185] Comparative Example 2
[0186] A positive electrode active material, a positive electrode, and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that a second positive electrode active material was prepared by designing the content (e.g., amount) of yttrium in the coating to be 1.5 mol % based on 100 mol % of the total metal other than lithium in the final second positive electrode active material.
[0187] Comparative Example 3
[0188] A positive electrode active material, a positive electrode, and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the second positive electrode active material was prepared by not using aluminum oxide during coating, ie, the coating of the second positive electrode active material did not include aluminum.
[0189] Comparative Example 4
[0190] A positive electrode active material, a positive electrode, and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the second positive electrode active material was prepared by designing the content (e.g., amount) of aluminum in the coating to be 3 mol % based on 100 mol % of the total metals other than lithium in the final second positive electrode active material.
[0191] Reference Example 1
[0192] The first positive electrode active material was prepared as follows. 0.75 Mn0.25 (OH)2, LiOH and Al2O3 were mixed in a molar ratio of 1:1:0.02 and then heat-treated at 850°C for 8 h in an oxygen atmosphere to prepare a molten-silicon composite with an average particle size (D 50 ) in the form of secondary particles of about 14 μm having LiNi 0.75 Mn 0.23 Al 0.02 The first composite oxide was mixed with alumina powder and zirconium oxide powder, and then heat-treated at 825° C. for 8 hours in an oxygen atmosphere and dried to prepare a first positive electrode active material coated with Al and Zr.
[0193] A positive electrode active material, a positive electrode, and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the first positive electrode active material was used to prepare the positive electrode active material.
[0194] Reference Example 2
[0195] A positive electrode active material, a positive electrode, and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the first positive electrode active material was prepared by not using aluminum sulfate during coating, ie, the coating of the first positive electrode active material did not include aluminum.
[0196] Reference Example 3
[0197] A positive electrode active material, a positive electrode, and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the first positive electrode active material was prepared without being coated with zirconium, ie, zirconium oxide was not added during the secondary heat treatment.
[0198] For better understanding, the design details of the positive electrode active materials of Examples, Comparative Examples, and Reference Examples are briefly shown in Table 1.
[0199] (Table 1)
[0200]
[0201]
[0202] Evaluation Example 1
[0203] At 25°C, each of the rechargeable lithium battery cells obtained in the embodiments, comparative examples and reference examples was charged to 4.45V at a constant current of 0.2C, charged to 0.05C at a constant voltage, and discharged to a cut-off voltage of 3.0V at 0.2C to perform initial charge and discharge to measure the initial discharge capacity, and the results are shown in Table 1.
[0204] Subsequently, each of these battery cells was repeatedly charged 50 times or more at 1.0C in a voltage range of 3.0V to 4.45V at 45°C and discharged at 1.0C to calculate the ratio of the 50th cycle discharge capacity to the initial discharge capacity (ie, cycle life), and the results are shown in Table 1.
[0205] In addition, the density of the positive electrode active material layer in each of the positive electrodes in the pressed state of the examples, comparative examples, and reference examples was measured, and the results are shown in Table 1.
[0206] Referring to Table 1, the Examples each achieved excellent or appropriate initial discharge capacity and relatively high density of the positive electrode active material layer in the positive electrode while maintaining or further improving cycle life characteristics compared to the Comparative Examples.
[0207] In the present disclosure, "not including one or any 'component'", "excluding one or any 'component'", "no 'component'", etc. means that the "component" is not added, selected or utilized as a component in the composition / element / structure. However, in some embodiments, due to other impurities and / or external factors, the "component" may still be included in an amount less than the appropriate amount.
[0208] As used herein, the terms "substantially," "about," and similar terms are used as terms of approximation rather than as terms of degree, and are intended to account for the inherent deviations in measured or calculated values that would be recognized by one of ordinary skill in the art. Also, "about" or "approximately" as used herein include the stated value and mean within an acceptable range of deviation for the particular value determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" may mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the stated value.
[0209] Any numerical range set forth in this article is intended to include all sub-ranges of the same numerical precision contained in the range of the setting forth. For example, the range of "1.0-10.0" is intended to include all sub-ranges (and end values) between the minimum value 1.0 set forth and the maximum value 10.0 set forth, that is, a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as, for example, 2.4-7.6. Any maximum numerical limit set forth herein is intended to include all lower numerical limits contained therein, and any minimum numerical limit set forth in this specification is intended to include all higher numerical limits contained therein. Accordingly, the applicant reserves the right to modify this specification (including claims) to explicitly set forth any sub-ranges contained in the range explicitly set forth herein.
[0210] The battery management system (BMS) device and / or any other related device or component according to the embodiments of the present invention described herein may be implemented using any appropriate hardware, firmware (e.g., a dedicated integrated circuit), software, or a combination of software, firmware, and hardware. For example, the various components of the device may be formed on an integrated circuit (IC) chip or on a separate IC chip. In addition, the various components of the device may be implemented on a flexible printed circuit film, a tape carrier package (TCP), or a printed circuit board (PCB), or formed on a substrate. In addition, the various components of the device may be processes or threads running on one or more processors in one or more computing devices, executing computer program instructions and interacting with other system components to perform the various functions described herein. The computer program instructions are stored in a memory, which may be implemented in a computing device using a standard memory device, such as, for example, a random access memory (RAM). The computer program instructions may also be stored in other non-temporary computer-readable media (such as, for example, a CD-ROM, a flash drive, etc.). Moreover, those skilled in the art should recognize that, without departing from the scope of the present disclosure, the functions of various computing devices may be combined or integrated into a single computing device, or the functions of a dedicated computing device may be distributed on one or more other computing devices.
[0211] Although the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it should be understood that the present disclosure should not be limited to the disclosed embodiments. Instead, the present disclosure is intended to cover one or more suitable modifications and equivalent arrangements included within the spirit and scope of the claims and their equivalents.
Claims
1. A positive electrode active material comprising: a first positive electrode active material including a lithium nickel manganese-based composite oxide having a nickel content of greater than or equal to 60 mol % based on 100 mol % of total metals other than lithium in the first positive electrode active material and in the form of a plurality of secondary particles each including a plurality of primary particles, and a second positive electrode active material including a lithium nickel manganese-based composite oxide having a nickel content of greater than or equal to 60 mol % based on 100 mol % of the total metals other than lithium in the second positive electrode active material and in the form of a plurality of single particles, wherein the second positive electrode active material includes a coating layer on a surface of each of the plurality of individual particles and comprising aluminum and yttrium, and The aluminum content of the coating layer is 0.1 mol % to 2 mol % and the yttrium content of the coating layer is 0.1 mol % to 1 mol % based on 100 mol % of total metals except lithium in the second positive electrode active material.
2. The positive electrode active material according to claim 1, wherein The average particle size D of the secondary particles of the first positive electrode active material 50 is larger than the average particle size D of the single particles of the second positive electrode active material. 50 .
3. The positive electrode active material according to claim 1, wherein The average particle size D of the secondary particles of the first positive electrode active material 50 10μm to 20μm, and The average particle size D of the single particles of the second positive electrode active material 50 0.5μm~8μm.
4. The positive electrode active material according to claim 1, wherein Based on 100 wt % of the first positive electrode active material and the second positive electrode active material in total, The amount of the first positive electrode active material is 60 wt% to 95 wt%, and The amount of the second positive electrode active material is 5 wt % to 40 wt %.
5. The positive electrode active material according to claim 1, wherein The lithium nickel manganese composite oxide of the first positive electrode active material and the lithium nickel manganese composite oxide of the second positive electrode active material are the same or different, and each independently has a nickel content of 60 mol % to 80 mol % based on 100 mol % of total metals other than lithium in each corresponding lithium nickel manganese composite oxide.
6. The positive electrode active material according to claim 1, wherein The lithium nickel manganese composite oxide of the first positive electrode active material and the lithium nickel manganese composite oxide of the second positive electrode active material are each independently a lithium nickel manganese aluminum composite oxide further including aluminum in addition to nickel and manganese, and The content of aluminum in each of the corresponding lithium nickel manganese aluminum-based composite oxides is 1 mol % to 3 mol % based on 100 mol % of total metals except lithium in each of the corresponding lithium nickel manganese aluminum-based composite oxides.
7. The positive electrode active material according to claim 1, wherein The lithium nickel manganese based composite oxide of the first positive electrode active material and the lithium nickel manganese based composite oxide of the second positive electrode active material each independently have a cobalt content of 0 mol % to 0.01 mol % based on 100 mol % of total metals other than lithium in each corresponding lithium nickel manganese based composite oxide.
8. The positive electrode active material according to claim 1, wherein The lithium nickel manganese composite oxide of the first positive electrode active material and the lithium nickel manganese composite oxide of the second positive electrode active material are each independently represented by Chemical Formula 1: Chemical formula 1 Li a1 Ni x1 Mr y1 Al z1 M 1 w1 O 2-b1 X b1 , In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W and Zr, and X is one or more elements selected from F, P and S.
9. The positive electrode active material according to claim 8, wherein In Chemical Formula 1, the positive electrode active material satisfies 0.6≤x1≤0.8, 0.1≤y1≤0.39, 0.01≤z1≤0.03, and 0≤w1≤0.
29.
10. The positive electrode active material according to claim 1, wherein The first positive electrode active material further includes a coating layer on a surface of each of the secondary particles and including aluminum and zirconium.
11. The positive electrode active material according to claim 10, wherein The coating layer has an aluminum content of 0.1 mol% to 2 mol% based on 100 mol% of total metals excluding lithium in the first positive electrode active material, and The zirconium content of the coating layer is 0.05 mol % to 1 mol % based on 100 mol % of total metals excluding lithium in the first positive electrode active material.
12. The positive electrode active material according to claim 10, wherein The aluminum content of the coating layer of the first positive electrode active material is greater than the aluminum content of the coating layer of the second positive electrode active material.
13. The positive electrode active material according to claim 12, wherein The ratio of the aluminum content of the coating layer of the first positive electrode active material to the aluminum content of the coating layer of the second positive electrode active material is 5:1 to 2:
1.
14. The positive electrode active material according to claim 10, wherein The coating layer of the first positive electrode active material is in the form of a shell that continuously surrounds the surface of each of the secondary particles.
15. The positive electrode active material according to claim 10, wherein The coating layer of the first positive electrode active material has a thickness of 30 nm to 500 nm.
16. The positive electrode active material according to claim 10, wherein The coating layer of the first positive electrode active material further contains yttrium.
17. The positive electrode active material according to claim 10, wherein The coating layer of the first positive electrode active material is on the surface of each of the primary particles inside each of the secondary particles and further includes a grain boundary coating layer including aluminum.
18. The positive electrode active material according to claim 1, wherein The coating layer of the second positive electrode active material is in the form of a shell that continuously surrounds the surface of the single particle.
19. The positive electrode active material according to claim 1, wherein The coating layer of the second positive electrode active material has a thickness of 30 nm to 500 nm.
20. The positive electrode active material according to claim 1, wherein In the coating layer of the second positive electrode active material, the aluminum exists in the form of a continuous film and the yttrium exists in the form of islands.
21. The positive electrode active material according to claim 1, wherein The second positive electrode active material includes a first coating layer on the surface of each of the plurality of individual particles and including aluminum, and a second coating layer on the first coating layer and including yttrium.
22. The positive electrode active material according to claim 1, wherein The positive electrode active material does not contain sodium.
23. A positive electrode comprising: a positive electrode current collector, and A positive electrode active material layer is provided on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 22.
24. The positive electrode of claim 23, wherein The positive electrode active material layer has a density of 3.5 g / cc to 3.7 g / cc.
25. A rechargeable lithium battery comprising The positive electrode according to claim 23 or 24, negative electrode, and Electrolyte.
26. The rechargeable lithium battery of claim 25, wherein: The charging voltage of the rechargeable lithium battery is greater than or equal to 4.45V.
Citation Information
Patent Citations
Method and terminal for triggering BFR procedure in multi beam system
KR1020230101765A